Nuclear Maturation Competence and Pronuclear Formation in Ovine Oocytes Supplemented with L-ergothioneine in Maturation Medium - Rimas Prathita Agustin; Mohamad Agus Setiadi; Iman Supriatna (Jurnal Ilmu Ternak dan Veteriner, 2023)
This study aimed to determine the efficacy of supplementing maturation medium with L-ergothioneine on nuclear maturation competence and pronuclei formation of ovine oocytes in vitro.  In the first study, oocytes were divided into four groups and matured for 24 hours in a maturation medium supplemented with 0 mM (control), 10 mM, 15 mM, and 20 mM LE.  In the second study, oocytes were divided into two groups and matured for 24 hours in a maturation medium supplemented with 0 mM LE (control) and 10 mM LE (optimal dose from the first study), then co-incubated with sperm in a fertilization medium for 12 hours.  The results of the first study showed that the maturation rate of oocytes enriched with LE 10 mM (88.74±1.79%) and 15 mM (87.52±2.30%) in maturation medium was significantly different (P0.05) compared to the control (78.55±1.78%) and LE 20 mM (77.37±1.21%).  Furthermore, the results of the second study revealed that the fertilization rate of oocytes with 10 mM LE (75.55±3.47%) supplementation in maturation medium had a significantly higher percentage of two pronuclei formation than control (63.78±3.49%).  In conclusion, supplementing 10 mM LE in a maturation medium improved oocyte nuclear maturation competence and fertilization rates.